Assessment of milk quality and the potential of a quality based payment system in smallholder farms in Limuru and Eldoret, Kenya - Kabui, K.K. (University of Nairobi, 2012)
The dairy sub-sector in Kenya accounts for 14% of the agricultural gross domestic product (GDP) and 3.5% of the national GDP. The sub-sector is mainly made up of small scale dairy farmers who are scattered in high and medium potential areas of the country (USAID report, 2008). These small scale farmers account for approximately 75% of the milk produced which is currently estimated to be more than four billion liters (FAO stat, 2011). Most of this milk is informally marketed and paid for based on quantity. Public health concerns have been raised on the quality of this milk and considering that consumers were found willing to pay more for improved milk safety and quality attributes, the safety and quality of the milk produced by small scale dairy farmers who are the predominant players in the dairy industry has to be guaranteed in order to enable them retain and access convectional markets. This study was conducted in Limuru and Eldoret to determine the quality of milk produced by small scale farmers and their perceptions on a quality based milk payment system. The study design was cross sectional where 297 individual and 10 bulk milk samples were systematically sampled and 252 questionnaires administered at the household level for both study areas. Direct and indirect bacteriological analysis was done using the total count, coliform count, titratable acidity and resazurin tests. Compositional analysis was done by testing for the fat content, solids not fat (SNF), density, protein and added water using a milk analyzer (Lactoscan). A questionnaire on farmer practices was administered at the household level to assess knowledge on milk hygiene aspects and perceptions on quality based milk payment system. The results obtained from the assessment of the bacteriological and compositional quality were judged against the Kenya Bureau of Standards (KeBS) bench marks. Of the milk samples collected in Limuru, 78% and 91% were of good quality based on total counts (≤ 2 million cfu/ml) and coliform counts (≤ 50,000 cfu/ml) respectively. From Eldoret, 78% and 92% of the milk samples were of good quality based on the same benchmarks for total and coliform counts, respectively. Analysis using the resazurin test indicated that 77% and 83% of the samples from Eldoret and Limuru respectively had readings ranging from 4-6 on the Lovibond comparator indicating that the milk was of good acceptable quality. Eighty percent of the samples from Limuru were found to have acidity levels within the acceptable range of 0.16±0.02 and therefore judged to be of good quality for the titratable acidity test. The compositional analysis results from Limuru showed that the average pH was 6.63, fat 3.8%, density 1.027 g/ml, protein 3.1%, freezing point -0.541o C, added water 3.42% and solids not fat 8.2%. The average pH, fat and the freezing point were within the recommended ranges while the SNF, protein and density were below the recommended ranges. Added water was above the limit set indicating presence of adulteration. The compositional analysis for Eldoret samples showed that the average pH was 6.64, fat was 4.28%, density was 1.028, protein was 3.64%, freezing point was -0.556, added water was 1.88% and solids not fat was 9.23%. The average pH, fat, density, protein and freezing point were within the recommended levels while added water was above the limit due to adulteration. A correlation analysis between the direct and indirect bacteriological tests showed that there was a significant positive correlation between the resazurin test and the total count(r = 0.70; p<0.05 and r =0.25; p<0.05) and coliform count (r = 0.55; p<0.05 and r =0.23; p<0.05) in both study areas. Results from the questionnaire survey revealed that most farmers (84 % in Limuru and 98% in Eldoret) would accept a system of payment on quality provided there was appropriate incentive. Most farmers (82%) were also found to be adhering to recommended dairy hygiene practices such as washing the milk cans with hot water and soap. Regression analysis at a significance level of 5% showed that none of the independent variables investigated contributed significantly to the quality of the milk. The overall milk quality from both study areas could be termed as acceptable based on the KeBS benchmarks. This could have been related to good dairy farmer practices that were observed such as hand washing, timely removal of manure, proper cleaning of milk cans and use of recommended bedding material. Continued application of these practices would help in improvement of the quality of milk and decrease losses due to rejected milk. The study concludes that it is possible to introduce a system of milk payment on quality where the resazurin test can be introduced as a screening test for the bacteriological quality at the milk collection centre level. It is recommended that a pilot study be conducted to test the applicability of such a system.